A food-based low-energy, low-carbohydrate diet for people with type 2 diabetes in primary care: a randomised controlled feasibility trial - Morris, E; Aveyard, P; Dyson, P; Noreik, M; Bailey, C; Fox, R; Jerome, D; Tan, GD; Jebb, SA (Wiley, 2019)
AIMS:Low-energy and low-carbohydrate diets may improve glycaemic control in people with diabetes, but trials have tested interventions that are delivered by specialists or used meal replacement products. As most people with diabetes are cared for in primary care, and total diet replacement programmes are not widely available, we examined the feasibility of a food-based low-energy, low-carbohydrate diet with behavioural support delivered by practice nurses for patients with type 2 diabetes. MATERIALS AND METHODS:People with type 2 diabetes and BMI≥30kg/m2 were randomised 2:1 to intervention or control (usual care) and assessed at 12 weeks. The intervention comprised an 800-1000kcal/d, food-based low-carbohydrate (<26% energy) diet for eight weeks, followed by a four-week weight maintenance period, and four 15-20 minute appointments with a nurse. Primary outcomes were feasibility of recruitment, fidelity of intervention delivery, and retention of participants at 12 weeks. Secondary outcomes included change in weight and HbA1c. Focus groups explored intervention experience. RESULTS:48 people were screened, 33 enrolled, and 32 followed up. Mean(±SD) weight loss in the intervention group was 9.5kg(±5.4kg), compared with 2kg(±2.5kg) in the control group (difference -7.5kg (-11.0 to -4.0, p<0.001)). Mean reduction in HbA1c in the intervention group was 16.3mmol/mol(±13.3mmol/mol), compared with 0.7mmol/mol (±4.5mmol/mol) in the control group (difference -15.7mmol/mol(-24.1 to -7.3, p<0.001)). CONCLUSIONS:It is feasible to recruit participants to a food-based low-energy, low-carbohydrate intervention, for practice nurses to deliver the programme in primary care, and to retain participants in both groups. There is evidence of clinically significant short-term improvements in weight and glycaemic control. This article is protected by copyright. All rights reserved.